CELAH IPV6 ROUTER ADVERTISEMENT PADA SISTEM OPERASI WINDOWS - Yadi, Ilman Zuhri ; Kunang, Suzi Oktavia (JURNAL ILMIAH MATRIK, 2018)
With the decrease in the number of IPv4 available it is necessary to consider IPv6 usage. However, IPv6 itself still has security holes such as security flood hole Router Advertisement false. Router Advertisement flood itself is an IPv6 DoS attack on the local network. This attack floods the local network segment with malicious Router Advertisement to replace the legitimate routing entry on the host interface. The purpose of this research is to study the response of Operating System with Windows platform against IPv6 Router Advertisement attack on the network, and to recommend solution to close the security hole. Attack testing is done with two stages of RA flood packet delivery with single prefix and multi prefix. Keywords: Router Advertisement, IPv6, Sistem Operasi